Skilled Bimanual Training Drives Motor Cortex Plasticity in Children With Unilateral Cerebral Palsy. (October 2016) - Friel, Kathleen M.; Kuo, Hsing-Ching; Fuller, Jason; Ferre, Claudio L.; Brandão, Marina; Carmel, Jason B.; Bleyenheuft, Yannick; Gowatsky, Jaimie L.; Stanford, Arielle D.; Rowny, Stefan B.; Luber, Bruce; Bassi, Bruce; et al.
Background . Intensive bimanual therapy can improve hand function in children with unilateral spastic cerebral palsy (USCP). We compared the effects of structured bimanual skill training versus unstructured bimanual practice on motor outcomes and motor map plasticity in children with USCP. Objective . We hypothesized that structured skill training would produce greater motor map plasticity than unstructured practice. Methods . Twenty children with USCP (average age 9.5; 12 males) received therapy in a day camp setting, 6 h/day, 5 days/week, for 3 weeks. In structured skill training (n = 10), children performed progressively more difficult movements and practiced functional goals. In unstructured practice (n = 10), children engaged in bimanual activities but did not practice skillful movements or functional goals. We used the Assisting Hand Assessment (AHA), Jebsen-Taylor Test of Hand Function (JTTHF), and Canadian Occupational Performance Measure (COPM) to measure hand function. We used single-pulse transcranial magnetic stimulation to map the representation of first dorsal interosseous and flexor carpi radialis muscles bilaterally. Results . Both groups showed significant improvements in bimanual hand use (AHA; P < .05) and hand dexterity (JTTHF; P < .001). However, only the structured skill group showed increases in the size of the affected hand motor map and amplitudes of motor evoked potentials ( P < .01). Most children who showed the most functional improvements (COPM) had the largest changes in map size. Conclusions . These findings uncover a dichotomy of plasticity: the unstructured practice group improved hand function but did not show changes in motor maps. Skill training is important for driving motor cortex plasticity in children with USCP.